Relationship Among Ceo Characteristics, Concentrated Ownership And Earnings Management: The Case Of Jordanian Companies - Al-begali, Safia Abdo Ali (2024)
In recent years, the issue of earnings management has garnered significant attention from researchers and academics due to its consequences on the quality of financial reports and its impact on investors' decision-making. This study aims to provide evidence on the influence of COVID-19, CEO characteristics, and ownership concentration on two forms of earnings management (EM), namely accruals-based earnings management (AEM) and real earnings management (REM) in Jordan. Additionally, the study explores the role of ownership concentration (family and foreign ownership) as a moderating variable in the relationship between CEO characteristics and earnings management. The study sample included all service and industrial companies listed on the Amman Stock Exchange (ASE) after the update of the Jordanian Corporate Governance Code (JCGC) 2017, covering the period from 2017 to 2021. The theoretical basis for understanding this relationship draws upon the agency, upper-echelons theories and the entrenchment and alignment effects. The hypotheses were tested using the feasible generalized least squares (FGLS) method to address heteroskedasticity and autocorrelation issues, as it provides a suitable approach for controlling these problems in the analysis. The results reveal a negative relationship between COVID-19, CEO tenure, and AEM practices in Jordanian companies. A negative relationship exists between CEO non-duality, CEO age, and REM practices. However, the study uncovers a positive relationship between CEO gender, CEO experience, CEO age, and AEM.